Managing "Stable" Cancer News. (March 2021) - Beach, Wayne A.
This study focuses on oncology interviews with returning patients who have been diagnosed with cancer, are undergoing various treatment regimens, and have been informed by doctors of their current "stable" medical condition. Conversation analysis was conducted on 112 video recorded and transcribed oncology interviews involving 30 doctors. In 44 of 112 (39 percent) interviews, doctors announced stable as good cancer news. In response, patients rarely affirm stable as good news for them. Nonreponses and minimal responses lacking enthusiasm occurred in one third of instances, and in the majority of interactions, patients resisted and questioned impacts of the need to endure ongoing treatments yet reduced possibilities for cancer shrinkage or remission. These interactional disjunctures reflect epistemic dilemmas for doctors seeking to provide quality care and especially for patients who must simultaneously manage good and bad news. Findings extend ongoing research and theoretical development that address the social psychological burdens inherent in disappointment, medical diagnosis, and prognosis. A focus on how patients and doctors manage stable cancer reveals recurring tensions between patients' lay experiences with illness and how doctors give biomedical priority to controlling cancer.